Establishing a Role for Minority Source Language in Multilingual Facilitation - Rueter, Jack; Partanen, Niko; Alnajjar, Khalid; Hämäläinen, Mika (Nordlyd, 2022)
This document is dedicated to a young man, who, despite the number of times he has traveled around the Sun, is always open to new thoughts on ways to include languages, especially the smaller ones, and the people who speak them in far-reaching and sustainable open-source development. Since Trond Trosterud in Tromsø is attributed a terrific track record in transnational and circum-polar linguistics, we try to attract his attention further afield, to languages and phenomena he has only touched. The language phenomena addressed here come from Erzya and the Zyrian variety of Komi; Erzya has issues presented but not discussed in his dissertation, whereas Komi brings in issues of adnominal and predicate number marking in conjunction with case homonymy that have been resolved thanks to the flexibility of the infrastructure. These source languages, like others, have documented new dimensions and added shape to the evergrowing infrastructure.